Age-related changes in biological characteristics of worker bees - Шамро, Л. П.; Шамро, Т. М. (Scientific Progress & Innovations, 2012)
The researches on the age-related changes of protein content in worker bees’ hemolymph, the grade of development of their pharyngeal glands and fat body were done. They showed that the potential supply of protein in hemolymph of late summer bees generation was not reduced with the age as in early summer bees generation and remained fairly stable. During the autumn period, the pharyngeal glands and fat body of bees are in developing and their grade reaches 3.56 and 2.65 points respectively what is typical for them in preparation for the wintering.